A dialogue between Haizi's poetry and the Gospel of Luke : Chinese homecoming and the relationship with Jesus Christ - Yang, Xiaoli. (Theology and Mission in World Christianity, 2018)
In A Dialogue between Haizi's Poetry and the Gospel of Luke Xiaoli Yang offers a conversation between the Chinese soul-searching found in Haizi's (1964-1989) poetry and the gospel of Jesus Christ through Luke's testimony. It creates a unique contextual poetic lens that appreciates a generation of the Chinese homecoming journey through Haizi's poetry, and explores its relationship with Jesus Christ. As the dialogical journey, it names four stages of homecoming-roots, vision, journey and arrival. By taking an interdisciplinary approach-literary study, inter-cultural dialogue and comparative theology, Xiaoli Yang convincingly demonstrates that the common language between the poet Haizi and the Lukan Jesus provides a crucial and rich source of data for an ongoing table conversation between culture and faith.